Attracting Generation Z: How Employer Attractiveness and Prestige Affect Application Decisions - Daniel Yudistya, Wardhana; Chrysilla Gita Astrellia, Angelina (Universitas Dinamika, 2024)
This study was conducted to investigate the influence of employer attractiveness and prestige on job intention to apply for higher education students in Yogyakarta. Data in this study was obtained through online questionnaires distributed to students, with a total of 78 validated answers. The multiple regression analysis used as the research methods using the SPSS software. The hypothesis results showed that there was no positive and significant influence between employer attractiveness on intention to apply. However, there is a positive and significant influence between employer prestige on the intention to apply.